Organizing adult attachment in alternative ways: A qualitative assessment of schemas antithetical to the secure base script - Shannon Maingot; Marije L. Verhage; Carlo Schuengel; Theodore E. A. Waters; Elja E. J. Meijer; Gabrielle Myre; Eva C. van Meeuwen; Glenn I. Roisman; Robbie Duschinsky; Marissa D. Nivison; Or Dagan; Victoria Zhu; et al. (PLoS ONE, 2026)
How adults make meaning of their childhood experiences with caregivers plays a central role in how they anticipate support, manage distress, and interpret relationships. To understand how adults conceptualize these attachment relationships, the Adult Attachment Interview (AAI) probes for childhood memories of general relationships, day-to-day interactions, and instances of loss, threat, and separation. Across these narratives, the AAI captures expectations of whether caregivers are perceived as an available source of support in times of distress, and whether they serve as a secure base from which to seek comfort and explore the world. Developing a coding system for secure base script knowledge, based on the AAI (AAIsbs), Waters, and Facompré also identified alternative, schema-like representations that seemed to conflict with the secure base script. Before exploring empirical questions regarding these alternative schemas, the present study undertook a qualitative systematic examination of their content in a large, risk-diverse corpus of interviews from 14 studies. Conducting a thematic analysis, 1,592 AAIs were examined by seven trained coders. This resulted in the identification of three novel themes (Favoritism, Incompetent, and Restrictive), the amendment of three existing schemas (Caregiver Source of Distress, Harsh and Threatening Parenting, and Self-Involved), and the replication of evidence for existing schemas. Together, the diversity and thematic coherence of alternative schemas underscore how relational expectations may be organized around vigilance, distress, or self-reliance, rather than comfort and support. This study contributes to theory-building on relational representations by expanding our understanding of how caregiving relationships are cognitively structured under conditions of relational adversity.